Differences on Primary Care Labor Perceptions in Medical Students from 11 Latin American Countries - Pereyra Elías, Reneé (2016)
Background The shortage in Latin-American Primary Care (PC) workforce may be due to negative perceptions about it. These perceptions might be probably influenced by particular features of health systems and academic environments, thus varying between countries. Methods Observational, analytic and cross-sectional multicountry study that evaluated 9,561 first and fifth-year medical students from 63 medical schools of 11 Latin American countries through a survey. Perceptions on PC work was evaluated through a previously validated scale. Tertiles of the scores were created in order to compare the different countries. Crude and adjusted prevalence ratios were calculated using simple and multiple Poisson regression with robust variance. Results Approximately 53% of subjects were female; mean age was 20.4±2.9 years; 35.5%were fifth-year students. Statistically significant differences were found between the study subjects’ country, using Peru as reference. Students from Chile, Colombia, Mexico and Paraguay perceived PC work more positively, while those from Ecuador showed a less favorable position. No differences were found among perceptions of Bolivian, Salvadoran, Honduran and Venezuelan students when compared to their Peruvian peers. Conclusions Perceptions of PC among medical students from Latin America vary according to country. Considering such differences can be of major importance for potential local specific interventions.